The Effect Of Work Discipline And Work Environment Of Civil Servants On Civil Servant Performance At BKPSDM Metro City - Mega Agista; Tina Miniawati Virgawenda Barusman (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the effects of work discipline and work environment on the performance of Civil Servants (Pegawai Negeri Sipil/PNS) at the Human Resources and Human Resource Development Agency (Badan Kepegawaian dan Pengembangan Sumber Daya Manusia/BKPSDM) of Metro City. The study employs a quantitative approach using a survey method. The research population consists of all civil servants at BKPSDM Metro City, with total sampling applied as the sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that work discipline has a positive and significant effect on employee performance, with a calculated t-value of 3.409 and a significance level of 0.001 (< 0.05). The work environment also shows a positive and significant effect on employee performance, with a calculated t-value of 4.056 and a significance level of 0.000 (< 0.05). Simultaneous testing results demonstrate that work discipline and the work environment jointly have a significant effect on employee performance. These findings suggest that improvements in the performance of civil servants at BKPSDM Metro City can be achieved through the consistent implementation of work discipline and the creation of a conducive and comfortable work environment.